Zmĕny psychovizuálních funkcí po centrální serózní chorioretinopatii - Bartos, D; Kondrová, J; Stibor, V; Bartosová, L; Rousová, A (Ceska a slovenska oftalmologie, 1998)
Psychovisual examination methods detect macular changes better and more subtly then hitherto commonly used examination methods, in particular in dynamic investigations. The authors used this method in a series of investigations of diabetes, glaucoma and haemodialysis. The group is formed by 19 eyes of 16 patients with a first attack of central serous chorioretinopathy. Two thirds of the patients were treated by conservative methods, one third by photocoagulation with an argon laser. The observation period was 3 months to 13 years, the mean being 3.5 years. The control group was formed by a group of healthy subjects of corresponding age. The authors proved a statistically significant (5%) reduction of the contrast sensitivity at medium spatial frequencies (6 and 12 c/dg) in patients with one or several attacks of CSCHR. Statistically significant deterioration of colour discrimination (5%) was proved in patients with one attack of CSCHR in 20% of the patients. In patients with two or more attacks of the disease the authors recorded a statistically significant deterioration of colour discrimination (1%) in 44% of the patients. They did not reveal, using psychovisual examination methods, statistically significant differences between groups of patients treated conservatively or by laser. In all cases of impaired colour discrimination a disorder in the blue-yellow region was involved, i.e. in the region of retinal receptors.
Keywords: Contrast Sensitivity; Retinal Diseases; citlivost na kontrast; Female; vnímání barev; dospělí; Adult; nemoci retiny; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; Middle Aged; lidé středního věku; Color Perception; nemoci choroidey; Choroid Diseases